First report of Puto barberi (Cockerell) (Hemiptera: Putoidae) in the ornamental Ixora coccinea (L.) in Ecuador (Bioagro, 2024)
We present the first registration of Puto barberi (Hemiptera: Putoidae) associated with the ornamental species Ixora coccinea L. in the city of Guayaquil, Ecuador. The symtoms of the attack are characterized by yellowing, necrosis and loss of the plant leaves.
Keywords: Ixora; ornamental plants; pirate mealybug